A novel de novo germline mutation Glu40Lys in AKT3 causes megalencephaly with growth hormone deficiency. Issue 4 (12th February 2017) - Takagi, Masaki; Dobashi, Kazushige; Nagahara, Keiko; Kato, Mitsuhiro; Nishimura, Gen; Fukuzawa, Ryuji; Narumi, Satoshi; Hasegawa, Tomonobu
Abstract : Germline or somatic gain‐of‐function mutations in the v‐akt murine thymoma viral oncogene homolog 3 ( AKT3 ) have been reported to cause syndromic megalencephaly. We describe a novel germline mutation, p.Glu40Lys, in AKT3 . Phenotypically, the patient presented with megalencephaly with hypotonia, apparent connective tissue laxity, and growth hormone (GH) deficiency. To our knowledge, this is the first instance of a patient with megalencephaly with GH deficiency, harboring a germline de novo mutation in AKT3 . © 2017 Wiley Periodicals, Inc.